THE MAKING OF GUESS ME GAME CHALLENGE TO LEARN VOCABULARY FOR JUNIOR HIGH SCHOOL STUDENTS - Khusnul Imami; Abdul Malik (Politeknik Negeri Bengkalis, 2020)
As a phenomenon that many students are not so interested in the subject of English. One of the causes is lack of supporting media used by teachers to support the learning process. Students get bored in learning process because some teachers are book-minded. This project deals with The Making of Guess Me Game Challenge to Learn Vocabulary for Junior High School students. The formulation of the problem is how to make Guess Me Game Challenge. The study belongs to descriptive research. The purpose of this study is to make Guess Me Game Challenge to help student in learning vocabulary. There are two components in this game; they are self-made and expert-made components. The conclusions made after the making process of this game are the making processes of Guess Me Game Challenge. The results of this study are Boards, Clue Cards, Nametag and Figures.Â Keywords: Guessing Game, Vocabulary, Junior High School Students